CREATIVE WORKS OF ALISHER NAVOI (Academicia Globe: Inderscience Research, 2021)
The article, based on the study of historical sources of the time of Navoi, extensively covers the creative works of the great poet of the East and statesman Alisher Navoi (Khondamir, Muhammad Khivaki, Navoi, Babur) in the field of architecture, urban planning, landscape art and landscaping works carried out by him in Herat and other territories of Khorasan. It is reported that Navoi built mosques, madrasahs, hospitals, Khanaqah, Langarkhana, caravanserais, baths, Rabats, ponds, bridges, dug wells and canals for the administration of the people and citizens ' comfort.By the author developed the first table on the objects constructed by AlisherNavoi, their location and territories based on specific examples.It is proved that Navoi was not only a great poet of the East, but also a great creator, that is, the architect of his time and people. It is proved that Navoi was not only a great poet of the East, but also a great creator, that is, the architect of his time and people.